Differentiation of innovation strategies of manufacturing firms in the New Member States: cluster analysis on firm level data - Wziątek-Kubiak, Anna; Balcerowicz, Ewa; Pęczkowski, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
This paper investigates the differences in innovation behaviour among manufacturing firms in three New Member States (NMS): the Czech Republic, Hungary and Poland. It is based on a survey of firms operating in four manufacturing industries: food and beverages, automotive, pharmaceuticals and electronics. The paper takes into account: innovation inputs in enterprises, cooperation among firms in R&D activities, the benefits of cooperation with business partners and innovation effects. Five types of innovation patterns that firms in the NMS introduce to improve competitive advantage were detected using a cluster analysis. They differ in terms of in-house innovation capabilities, their forms, the use of external sources of innovation, spillover absorption and economic performance. Interestingly, most of them are similar to the innovation patterns of firms in the incumbent EU member states. This seems to confirm Shorec and Verspagen's (2008) claim that, in the heterogeneity in firms' innovation behaviour, countries matter only to a certain extent. The paper shows that in the NMS the role of the two types of innovation sources - R&D and cooperation - are complementary rather than consist of the 'make-or-buy decision' (Veugelers, 1997) model. Although external knowledge is important in innovation activities, the benefits of using it are determined by in-house innovation capacities
Argumenta Oeconomica, 2013, Nr 2 (31), s. 117-150
Keywords: innovation modes; differentiation of innovative firms; strategy of innovation; strategia innowacji; innowacyjność przedsiębiorstw; polityka badawczo-rozwojowa